Performance, Carcass Traits, and Meat Composition of Broiler Chickens Fed Diet Containing Fish Oil and Vitamin E - Sumiati; Darmawan, A.; Hermana, W. (Tropical Animal Science Journal, 2022)
The study aimed to determine the efficacy of dietary vitamin E and fish oils on performance, carcass yield, cholesterol, omega-3, and omega-6 in the meats of broiler chickens. A total of 400 Lohmann day-old broiler chicks consisted of 200 males and 200 females were reared for 35 days. This experiment employed a completely randomized design with five treatments and four replicates. The treatments were T0: Control diet with 3% crude palm oil without vitamin E; T1: Diet containing 3% fish oil; T2: Diet containing 3% fish oil and 80 IU/kg vitamin E; T3: Diet containing 3% fish oil and 100 IU/kg vitamin E, and T4: Diet containing 3% fish oil and 120 IU/kg vitamin E. The result showed that dietary fish oil and vitamin E had no effect (p>0.05) on feed intake, body weight, weight gain, AME, AMEn, TME, and TMEn, but it tended to decrease the mortality rate. T3 significantly reduced (p